Implementation and evaluation of nationwide scale‐up of the Surgical Safety Checklist. Issue 2 (8th January 2019) - White, M. C.; Randall, K.; Capo‐Chichi, N. F. E.; Sodogas, F.; Quenum, S.; Wright, K.; Close, K. L.; Russ, S.; Sevdalis, N.; Leather, A. J. M.
Abstract : Background: The WHO Surgical Safety Checklist improves surgical outcomes, but evidence and theoretical frameworks for successful implementation in low‐income countries remain lacking. Based on previous research in Madagascar, a nationwide checklist implementation in Benin was designed and evaluated longitudinally. Methods: This study had a longitudinal embedded mixed‐methods design. The well validated Consolidated Framework for Implementation Research (CFIR) was used to structure the approach and evaluate the implementation. Thirty‐six hospitals received 3‐day multidisciplinary training and 4‐month follow‐up. Seventeen hospitals were sampled purposively for evaluation at 12–18 months. The primary outcome was sustainability of checklist use at 12–18 months measured by questionnaire. Secondary outcomes were CFIR‐derived implementation outcomes, measured using the WHO Behaviourally Anchored Rating Scale (WHOBARS), safety questionnaires and focus groups. Results: At 12–18 months, 86·0 per cent of participants (86 of 100) reported checklist use compared with 31·1 per cent (169 of 543) before training and 88·8 per cent (158 of 178) at 4 months. There was high‐fidelity use (median WHOBARS score 5·0 of 7; use of basic safety processes ranged from 85·0 to 99·0 per cent), and high penetration shown by a significant improvement in hospital safety culture (adapted Human Factors Attitude Questionnaire scores of 76·7, 81·1 and 82·2 per cent before, and at 4 and 12–18 months after training respectively; P < 0·001). Acceptability, adoption, appropriateness and feasibility scored 9·6–9·8 of 10. This approach incorporated 31 of 36 CFIR implementation constructs successfully. Conclusion: This study shows successfully sustained nationwide checklist implementation using a validated implementation framework. Abstract : Implementation works